NEW PERSPECTIVES ON ORBITALLY FORCED STRATIGRAPHY - Hinnov L.A. (My University, 2000)
This survey of the current status of research into Earth’s orbitally forced paleoclimatic record summarizes recent developments in the theory of Earth’s orbital parameters, and reviews how various techniques of data collection and analysis have fared in the search and recovery of orbital signals in ancient stratigraphy. The emerging significance of the quasi-periodicity of Earth’s orbital variations as a principal tool in the analysis of orbitally forced stratigraphy is discussed in detail. Five case studies are presented that illustrate new directions in research: (a) time series analysis of discontinuous strata; (b) measurement of ultra-high resolution stratigraphic signals; (c) new perspectives on the 100 kyr Pleistocene glaciation problem; (d) stratigraphic evidence for solar system resonance modes; and (e) evaluating Phanerozoic length of day from orbitally forced stratigraphy.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен